2011
DOI: 10.1155/2011/623710
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Ketamine versus Midazolam/Fentanyl Sedation in Children Undergoing GI Endoscopy

Abstract: Background. Ketamine sedation has been found superior by physician report to traditional sedation regimens for pediatric endoscopy. Goal. To objectively compare sedation with ketamine versus midazolam/fentanyl for children undergoing gastrointestinal endoscopy. Study. Patients received one of two regimens and were independently monitored using a standardized rating scale. Results. There were 2 episodes of laryngospasm during ketamine sedation. Univariate analyses showed patients sedated with ketamine (n = 17) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…45 This may be difficult to evaluate, partly because of different sedative protocols between hospitals, and synergistic effect should be considered if combination protocol is used. [46][47][48] Another possible reason is that there are a number of other factors that affect the requirement for sedatives, including biological factors such as genetic predisposition for individual pain thresholds and the requirement for analgesic drugs. 49 Some studies have revealed that using combination nonpharmacological interventions can decrease doses of sedative drugs.…”
Section: Discussionmentioning
confidence: 99%
“…45 This may be difficult to evaluate, partly because of different sedative protocols between hospitals, and synergistic effect should be considered if combination protocol is used. [46][47][48] Another possible reason is that there are a number of other factors that affect the requirement for sedatives, including biological factors such as genetic predisposition for individual pain thresholds and the requirement for analgesic drugs. 49 Some studies have revealed that using combination nonpharmacological interventions can decrease doses of sedative drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of excessive muscle activity with KBRs have been described in other studies even in patients that appeared to be well sedated at onset of EGD. 18 Extended procedure time in some of our patients undergoing diagnostic and therapeutic endoscopy partly accounted for observed prolonged PACU recovery time. Two patients (ages 3 and 15) in the KBR group developed severe emergence reactions and hallucinations after EGD and were treated with Precedex.…”
Section: Discussionmentioning
confidence: 87%
“… Jamal et al, 2011 [ 12 ], Roback et al, 2005 [ 13 ], McQueen et al, 2009 [ 14 ], Urbain et al, 2000 [ 15 ], Lightdale et al, 2011 [ 16 ], Krick et al, 2013 [ 17 ], Margaret et al, 2021 [ 18 ] …”
Section: Reviewmentioning
confidence: 99%